Strategy for Environmental Preservation of Residential Areas over Water through Plastic Waste Management to Become Paving Blocks - Arief Nugraha Pontoh; Raftonado Situmorang; Eko Agung Syaputra; Muhamad Fajrin Wahab (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Kampung Atas Air area has a high level of activity and economy because of its location close to the Floating Market and Speedboat Harbor which connects Balikpapan City with North Penajam Paser Regency. The amount of garbage scattered in the area shows a lack of understanding and concern for the community about waste management. To overcome this problem, we need a strategy to protect the environment, especially the management of plastic waste. In this activity, community empowerment will be carried out through counseling and mentoring methods in order to process plastic waste into paving blocks that can be economically beneficial. Evaluations carried out on the implementation before and after the activity through distributing questionnaires revealed that people's understanding of environmental hygiene, types of plastic waste, and how to process plastic waste into paving blocks is increasing.